"The System of Odd and Even Numbers": Lewis Namier the Diplomatic Historian. Issue 2 (3rd April 2021) - Otte, T.G.
ABSTRACT: Sir Lewis Namier has left a deep, if contested, imprint on studies of eighteenth-century British political history. Namier the student of great power relations, by contrast, has been largely allowed to slide into oblivion. It is a curious fate, for in his day his public profile as a commentator on international affairs was very high. This article attempts to reconstruct Namier as a diplomatic historian, the intellectual assumptions that underpinned his work, the manner in which he framed the study of European great power politics, and the methods he employed.